Intervención Urbano Arquitectónica de Vivienda Colectiva y Revitalización en el Parque Peñón Redondo de la Comuna 8 del Municipio de Neiva – Huila (2021)
This investigative work takes into account a social problem caused by the invasion of families in the Peñón Redondo sector of the 8th Commune of Neiva-Huila, which has been experiencing population growth, breaking into an area that at the beginning of its uses were not provided for housing, generating a social and economic problem; crime, unemployment, damage to an ecosystem, loss of a park and pollution in its different foci are participants. Through this investigation of studies related to social strategies with urban architectural solutions, for a vulnerable population with the aim of identifying what can be implemented in said sector. The work was developed through a qualitative and quantitative methodology implementing a zonal analysis of the general population. The information was compiled and subdivided into topics such as studies on vulnerable populations, socioeconomics, and associativity. The research highlights the most representative studies in the different contexts and that were taken as a methodological guide. It is concluded that strategies focused on housing, socio-economy, socioactivity and connectivity of the population should be implemented; mainly in ideas of decent housing and entrepreneurship, to improve the socio-economic quality of the population.